2020
DOI: 10.1101/2020.06.25.20138602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical modeling of the COVID-19 prevalence in Saudi Arabia

Abstract: The swift precautionary and preventive measures and regulations that were adopted by the Saudi authority has ameliorated the exponential escalation of the SARS-CoV-2 virus spread, decreased the fatality rate and critical cases of COVID-19. Understanding the trend of COVID-19 is crucial to establishing the appropriate precautionary measures to mitigate the epidemic spread. The aim of this paper was to modifying and enhancing the mathematical modeling to guide health authority and assist in an early assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…However, like our study they also observed increase in cases upon temporarily relaxation of curfew in May. Nevertheless, they still predicted the end of the epidemic on 29th of September [ 32 ], based on the same assumptions. However, their scenarios were disturbed as proven by our study, due to easing lockdown measures.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, like our study they also observed increase in cases upon temporarily relaxation of curfew in May. Nevertheless, they still predicted the end of the epidemic on 29th of September [ 32 ], based on the same assumptions. However, their scenarios were disturbed as proven by our study, due to easing lockdown measures.…”
Section: Discussionsupporting
confidence: 77%
“…Another study conducted in the KSA [ 32 ] used the ARIMA model and Logistic growth model to provide short and long-term COVID-19 predictions; their prediction were made assuming that the lockdown will remain, KSA residents would follow the recommended safety guidelines and non-pharmaceutical interventions would be maintained. Based on that assumptions they predicted the end of the epidemic by 5th of August in their first scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Elhassan and Gaafar reported that the swift precautionary, regulations and the preventive measures that were adopted by the Saudi authority has ameliorated the exponential rise of the spreading of COVID-19, reduced the death rate and decreased the critical COVID-19 cases [14].…”
Section: Resultsmentioning
confidence: 99%
“…Elhassan and Gaafar [ 21 ] developed both the ARIMA model and Logistic growth model to study the trend and to provide short and long-term forecasting of the prevalence COVID-19 cases in Saudi Arabia. The data analyzed in their study covered the period of 2 Mar to 21 Jun 2020.…”
Section: Literature Reviewmentioning
confidence: 99%